Mengenal Pendidikan Akhlak Menurut Ibn Miskawaih - nasih nasih nasih (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2018)
Ibn Miskawaih bases his principle of moral virtue on the "middle" theory (al-wasath), an action is said to be true if it is in the midst of extreme excesses and extremes of deprivation so that one can be called fair if he is able to place himself between persecution and persecution. In addition, humans should be able to avoid moral illness that always undermines their lives. If the disease can be avoided, true happiness will soon be achieved. The form of happiness in man is not only found in the soul, but also at the same time in the body. The perfection of happiness will be fulfilled if the human being can spread love and affection among each other. In order for that love and affection to blossom in every human being, he must be nurtured through moral education that began in childhood. keynote : Education, Moral